ANALISIS WACANA KRITIS IKLAN INDIA OLAY TOTAL EFFECTS DAN POWER DUO - Tri Eka Wahyuni (Unika Santu Paulus Ruteng, 2022)
Beauty is one of the essential matters in society. Since the Covid-19 pandemic, the awareness of taking care of skin health has increased significantly. It affects beauty industries and encourages them to continue innovating their products, for example, anti-aging skincare from Olay. Olay, a global beauty brand, launched two products to overcome signs of aging skin that have been introduced since the 90s, Olay Total Effects and Power Duo in a different era. This study focuses on the meaning-making by the advertiser and the language used to create beauty myths. The analysis of the subject used deconstruction by Derrida, Fairclough’s 3D model, and attitude in appraisal theory as a linguistic approach. Deconstruction of the text revealed the opposition reversal of the text. Fairclough’s 3D model was used to find the relationship between the text and social context. The result shows that using language helps Olay’s advertiser shift beauty values and maintain its belief about how beautiful skin should look. Findings also reveals that strategies used in advertisements are manufacturing consent through implication, showing deficiency, positive self-representation, celebrity endorsement, and motive words. The power of language also makes people believe what is said is the truth. Aging is not something new, and it is a natural phenomenon. Furthermore, this study will enhance our understanding of the use of language to create new consciousness and maintain it in society